Perlindungan Hukum Bagi Apoteker dalam Melakukan Pelayanan Kefarmasian Secara Elektronik Pasca Pemberlakuan Undang-Undang Kesehatan - Putra, I Made Agus Sunadi; Kartika, I Gusti Ayu Putri; Widiatedja, I Gusti Ngurah Parikesit; Astuti, Ika Widi (Universitas Medan Area, 2024)
Proper legal protection for pharmacists is crucial in ensuring the sustainability of safe, quality, and ethically sound pharmaceutical practices following the enactment of Law Number 17 of 2023 on Health (Health Law). The purpose of this study is to examine the legal protection for pharmacists in conducting electronic pharmaceutical services following Health Law. This research is a normative juridical legal study with conceptual and statutory approach. The results of the study indicate that legal protection for pharmacists in conducting electronic pharmaceutical services enshrined in Health Law is divided into two types of legal protection, namely preventive and repressive legal protection. Preventive legal protection in this health law can be seen through the provisions regarding the rights of pharmacists in conducting pharmaceutical practices, particularly in the context of electronic pharmaceutical practices. Furthermore, regarding repressive legal protection, there are stipulations regarding the dispute resolution process that must be undertaken by the parties involved in medical disputes through both litigation and non-litigation processes.